The Face-to-Face Encounter: Embodiment and Ethical Responsibility in Levinas' Phenomenology: Perjumpaan Tatap Muka: Kebertubuhan dan Tanggung Jawab Etis dalam Fenomenologi Levinas - Patrick, Arokiaraj Joseph (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2025)
This article shows how Emmanuel Levinas’s ethical philosophy departs from traditional Western metaphysics by rooting moral responsibility in the embodied encounter between corporeal subjects. Embodiment is key for both the ethical subject and the Other, with ethical consciousness arising from shared corporeal vulnerability. For Levinas, ethical obligation emerges in concrete, physical encounters with the Other, rather than abstract principles. Ethical responsibility arises in the face-to-face encounter with the embodied Other, where vulnerability and need are revealed. Ethical response involves embodied acts of goodness and substitution, where the subject takes on the suffering and needs of the Other. By orienting itself toward the Other, the being can break free from self-centeredness and the dangers of the ‘there is’, establishing its identity outside itself and experiencing liberation. Ultimately, Levinas's ethics demands a shift from abstract moral reasoning to an embodied, practical response to the Other's call, unfolding in the immediacy of human encounters and grounded in the corporeal reality of our existence. Abstrak Artikel ini hendak menunjukkan bagaimana etika Emmanuel Levinas yang menjangkarkan tanggung jawab moral pada perjumpaan antar subjek yang bertubuh melepaskan diri dari metafisika tradisional Barat. Kebertubuhan menjadi kunci dalam perjumpaan antara seorang subjek moral dengan Yang Lain, di mana kesadaran moral tumbuh dari kerentanan fisik mereka. Alih-alih dari prinsip-prinsip abstrak, kewajiban moral muncul dari perjumpaan fisik yang konkret. Dalam perjumpaan antar wajah tersebut, kerapuhan dan kebutuhan masing-masing tersingkap. Tanggung jawab moral terwujud dalam respons baik yang menubuh dan dalam substitusi, melalui mana subjek merengkuh penderitaan dan kebutuhan Yang Lain sebagai miliknya. Lewat keterarahan pada Yang Lain, ‘ada’ membebaskan diri dari ‘ada-di-sana’ (il y a) dan dari keterpusatan diri seraya menegaskan identitasnya di luar diri sendiri. Etika Levinas menuntut pergeseran dari penalaran moral yang abstrak menuju kepekaan praktis pada panggilan Yang Lain, yang hadir dalam perjumpaan langsung dan melibatkan realitas kebertubuhan manusia. Kata-kata kunci: kebertubuhan, tanggung jawab moral, Emmanuel Levinas, Yang Lain, perjumpaan tatap muka, substitusi